1986
DOI: 10.1007/bf00199803
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of Archean vein-type gold deposits with reference to the Larder Lake ‘break’ of Ontario and Quebec

Abstract: Abstract. The vein-type gold deposits of middle to late

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Kerrich and Watson (1984) studied the heavy oxygen isotope of quartz from the wall rocks and veins in the Macassa gold deposit and suggested a metamorphic model indicating the origin of the fluid to be largely metamorphic dehydration under conditions of moderate Eh and weak acidity. Hinse et al (1986) proposed a general theory of genesis for the Archaean vein-type mineralizations using the Kirkland Lake -Larder Lake break of northern Ontario and Quebec as a model. They suggested that gold and associated constituents derived as weathering products from mafic-ultramafic volcanics and were concentrated as sols and solutions in muddy surfacial accumulates and as cherty and pyritic evaporite residues.…”
mentioning
confidence: 99%
“…Kerrich and Watson (1984) studied the heavy oxygen isotope of quartz from the wall rocks and veins in the Macassa gold deposit and suggested a metamorphic model indicating the origin of the fluid to be largely metamorphic dehydration under conditions of moderate Eh and weak acidity. Hinse et al (1986) proposed a general theory of genesis for the Archaean vein-type mineralizations using the Kirkland Lake -Larder Lake break of northern Ontario and Quebec as a model. They suggested that gold and associated constituents derived as weathering products from mafic-ultramafic volcanics and were concentrated as sols and solutions in muddy surfacial accumulates and as cherty and pyritic evaporite residues.…”
mentioning
confidence: 99%